The Impact of Uzbek Phonetic Features on English Pronunciation Acquisition - Topvoldieva Dilbarkhon; Ikramova Saida (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
The main purpose of this article to analyze the influence of Uzbek Phonetic features on English pronunciation acquisition. By comparing the phonological systems of both languages, the article identifies key areas of challenges and provides pedagogical solutions to enhance English pronunciation competence in Uzbek EFL learners.